Are our babies off to a healthy start? The state of implementation of the Global strategy for infant and young child feeding in Europe - Irena Zakarija-Grković; Adriano Cattaneo; Maria Enrica Bettinelli; Claudia Pilato; Charlene Vassallo; Mariella Borg Buontempo; Helen Gray; Clare Meynell; Patricia Wise; Susanna Harutyunyan; Stefanie Rosin; Andrea Hemmelmayr; et al. (BMC, 2020)
Abstract Background To protect children's right to optimal nutrition, WHO/UNICEF developed a Global Strategy for Infant and Young Child Feeding, endorsed by all 53 WHO/EURO Member States. The World Breastfeeding Trends Initiative (WBTi) is a tool for monitoring implementation of the Global Strategy. It comprises 15 indicators, ten referring to policies and programmes, and five to feeding practices. Each is scored on a scale of 10, giving a total score of 150 for Global Strategy implementation. To date, 18 WHO/EURO Member States - Armenia, Austria, Belgium, Bosnia and Herzegovina, Croatia, France, Georgia, Germany, Italy, Lithuania, North Macedonia, Malta, Moldova, Portugal, Spain, Turkey, Ukraine and United Kingdom - have conducted a WBTi assessment and produced a report. Methods Between June 2018 and May 2019, all 18 WBTi European reports were carefully read and analysed by a group of national WBTi coordinators. Descriptive data analysis, including inter-country comparisons, was conducted using frequencies and percentages. This paper summarises the findings. The full 88-page report will be published on the WBTi website. Results Three-quarters of 18 European countries have adequate maternity protection, and two-thirds have breastfeeding initiation rates of 50% or higher. However, 'Preparedness and planning for appropriate and safe Infant and Young Child Feeding (IYCF) in emergencies' is seriously neglected. Breastfeeding duration is far below WHO recommendations, with an average of 8.7 months. Only three European countries have a budget allocated for implementing IYCF policies and plans, and a third currently have no Baby-friendly designated maternity facilities. Bottle feeding is prevalent, despite its inherent risks, monitoring of IYCF practices is inadequate, with most countries not routinely collecting data, and violations of the International Code of Marketing of Breast-milk Substitutes are commonplace. Conclusions European governments are not doing enough to protect, promote and support sound infant and young child feeding practices. Political commitment at the highest level and adequate funding are required to ensure optimal IYCF for Europe's babies. This report highlights worrying gaps, thereby providing governments, international organisations and other concerned parties with an opportunity to invest in priority areas and, by doing so, hopefully create a better future for our babies.